Performance of Anaerobic Reactor in Attached and Suspended Growth Mechanisms for the Removal of Tofu Wastewater - Rosvita Tri Jullyanti; H. Purnobasuki; T. Nurhariyati; F. N. Rachman; N. I. Oktavitri (IPTEK Journal of Proceedings Series, 2014)
This study assessed the removal efficiency of organic compounds in attached and suspended growth mechanisms when an anaerobic reactor was used to treat tofu wastewater. Parameters such as BOD (BiologicalOxygen Demand), TSS (Total Suspended Solid) and VSS (Volatile Suspended Solid) were measured. The assessments of removal efficiency were measuredby the amount of degradation of organic compounds caused by the microorganisms. The analyses were conducted for 14 days with a ratio of 40% air and 60% wastewater for the suspended growth mechanism. In attached growth, gravel served as the media at 30% from 60% of wastewater with 40% air. The removal efficiency of organic compounds measured as the decrease of BOD, TSS, and VSS – in suspended and attached growth. BOD in suspended growth decrease 5,55% while 76,46% in attached growth, TSS in suspended growth decrease 64,59% while increased 19,40% in attached growth, similar results occurred for VSS parameter decrease 2,04% while increased 31,53%. The increased result of TSS and VSS in attached growth caused of biofilm growth. In conclusion, BOD, TSS, and VSS decreased greater when the anaerobic treatment in attached growth was applied.